Bifurcation of new optical solitary wave solutions for the nonlinear long-short wave interaction system via two improved models of (G?/G) expansion method - Khater, Mostafa M. A.; Akbar, M. Ali; Akinyemi, Lanre; Jhangeer, Adil; Rezazadeh, Hading; İnç, Mustafa (Springer, 2021)
This study performs two recent methods on the nonlinear long-short wave interaction system (NLSWIS) to obtain novel formulas of solitary solutions representing an optical field that does not alter by multiplication a sensitive balance between the different terms impacts in the medium. Elastic medium is defined as the medium that can adjust in the figure due to a deforming strength and come back shape to its original form when the force eliminates. The wave is produced by vibrations that are a consequence of acoustic power. Also known as the sound wave, or acoustic wave. For examples of elastic mediums are air, water and so on. The improved (G'/G) expansion method and novel (G'/G) expansion method are implemented, which are considered as two general methods in this field. Applying these methods to many nonlinear partial differential equations gives diverse and different forms and configuration solutions that allow users of those two methods a large number of solutions that provide broader scope to use.
Keywords: NLSWIS; Improved (G '/G) expansion method; Novel (G '/G) expansion method; New structure of optical soliton (os); Exact and solitary traveling wave solutions (sws)